Differences in Measures of Strength and Dynamic Balance among Individuals with Lower-Limb Loss Classified as Functional Level K3 Versus K4 - Beisheim, Emma Haldane (Am J Phys Med Rehabil, 2019)
OBJECTIVE: For individuals with lower-limb loss (LLL), functional mobility (i.e. K-level) classification can be subjective. Performance-based outcome measures (OM) improve the objectivity of K-level assignment; therefore, this study aimed to determine differences in functional strength- and dynamic balance-based OM performance between K3- and K4-classified adults with LLL. DESIGN: Prosthetists used subjective information and prosthetic componentry to determine K-levels prior to OM testing for adults with a unilateral transtibial (n=50) or transfemoral amputation (n=17). OM [i.e., 5-Times Sit-to-Stand Test (5xSTS), Figure-of-8 Walk Test (F8WT), 360° Turn Test (360TT), and modified Four-Square Step Test (mFSST)] were administered by a blinded examiner. Univariate analyses of variance (ANOVAs) were used to evaluate between-subgroup differences. RESULTS: K4-classified participants with a unilateral transfemoral amputation performed better on all outcome measures when compared with K3-classified peers, whereas K4-classified individuals with a transtibial amputation performed better on the modified Four-Square Step Test compared with K3-classified peers (P < 0.050). CONCLUSION: K4-classified individuals demonstrated greater lower-extremity functional strength and better dynamic balance compared to K3-classified peers. To assist with K-level classification, clinicians should consider selecting OM that objectively differentiate between K-levels (i.e., mFSST for those with a unilateral transtibial or transfemoral amputation; 5xSTS, F8WT, and 360TT for those with a transfemoral amputation).